The Role of IgA and IgG anti-transglutaminase antibodies in the diagnosis of celiac disease in children - ILIE, LACRAMIOARA; POPA, ANDREEA; GOROFTEI, LARISA; MATACHE, ELENA ROXANA; ZAHARIA, ELIZA ANDREEA; CHELMU VODA, CRISTINA; AMBROSE, LENUTA; GRIGORE, IONICA; MIHALACHE, DANIELA; GURAU, GABRIELA; Voinescu, Doina Carina (Technium BioChemMed, 2023)
Aims: Diagnosing celiac disease in children presents various challenges for pediatricians in the various clinical stages. Thus, the diagnosis of cases increased significantly, although children did not always present symptoms or clinical signs of the disease. In support of the diagnosis, several factors come into play: screening, serological tests, awareness of the presence of celiac disease and the factors that favor its occurrence. Material and methods: We performed a retrospective study at the Pediatric Clinical Hospital "St. Ioan " Galati between January 1, 2014 and October 2022. In this study we included 2640 children with suggestive symptoms of celiac disease. Results: A number of 102 patients were diagnosed with celiac disease, recurrent abdominal pain being the most common symptom.